A new case of photoallergic contact dermatitis caused by benzophenones in magazine covers. (13th February 2022) - Samaran, Quentin; Raison‐Peyron, Nadia; Clark, Evangeline; Svedman, Cecilia; Dahlin, Jakob; Dereure, Olivier; Bruze, Magnus; Bourrain, Jean Luc
Abstract: Background: Allergic contact dermatitis (ACD) and photoallergic contact dermatitis (PACD) to benzophenone present in printing ink have been reported. However, precise chemical analyses and extended photo‐patch tests have not been performed in these cases. Objectives: To determine which components present in a magazine cover are responsible for a patient's skin reaction, to determine the primary sensitizer, and precisely diagnose ACD and PACD. Methods: After initial photo‐patch tests were performed on a patient with a history of reaction to magazine covers after sun exposure, gas chromatography–mass spectrometry and high‐performance liquid chromatography analyses of the magazine covers, and additional photo‐patch tests were performed. Results: The first photo‐patch test results confirmed PACD to ketoprofen and fenofibrate and evoked PACD to the magazine covers. 4‐methyl benzophenone (4‐MBP) and 1‐hydroxy‐cyclohexyl‐phenyl‐ketone (1‐HCPK) were found in the magazine cover. Additional photo‐patch tests confirmed PACD to 1‐HCPK and to benzophenone, and photo‐aggravated ACD to 4‐MBP. The primary sensitizer was ketoprofen. Conclusions: Benzophenones are present in a wide variety of products, without always being listed on the packaging. Patients previously sensitized to other ketones, such as ketoprofen, may react to benzophenones without being able to avoid contact with these molecules. New regulations may be needed for more efficient eviction advice. Abstract : Photoallergic contact dermatitis to covers of a magazine was diagnosed and thorough investigation was necessary to identify the haptens responsible. Chemical analyses of the covers revealed the presence of 4‐methyl benzophenone (4‐MBP) and 1‐hydroxy‐cyclohexyl‐phenyl‐ketone (1‐HCPK) Photo‐patch tests suggested photo‐aggravation of contact dermatitis to 4‐MBP and benzophenone, and photoallergy to 1‐HCPK and ketoprofen. Ketoprofen was the most likely primary sensitizer.